(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article contains opinions about the ways, methods and necessity of preparing future primary school teachers for innovative activities, as well as the modern stages of the development of the educational system